Multisystem Myotilinopathy, including Myopathy and Left Ventricular Noncompaction, due to the MYOT Variant c.179C>T. (14th May 2020) - Finsterer, Josef; Stöllberger, Claudia; Hasun, Matthias; Riedhammer, Korbinian; Wagner, Mathias
Abstract : Left ventricular hypertrabeculation/noncompaction is a myocardial abnormality of unknown etiology/pathogenesis, which is frequently associated with neuromuscular disorders or chromosomal defects. LVHT in association with a MYOT mutation has not been reported. The patient is a 72-year-old male with a history of strabismus in childhood, asymptomatic creatine-kinase elevation since age 42 years, slowly progressive lower limb weakness since age 60 years, slowly progressive dysarthria and dysphagia since age 62 years, and recurrent episodes of arthralgias and myalgias since age 71 years. He also had arterial hypertension, diverticulosis, hyperlipidemia, coronary heart disease, and a hiatal hernia with reflux esophagitis. Clinical exam revealed mild quadruparesis and proximal wasting of the legs. Whole exome sequencing revealed a known variant in the MYOT gene. Muscle biopsy, previously assessed as inclusion body myopathy, was compatible with the genotype after revision. Cardiologic work-up revealed a left anterior hemiblock, mild myocardial thickening, and noncompaction. This case shows that myotilinopathy may manifest as a multisystem disease, including noncompaction.